THE STUDY OF BIOCHEMICAL PARAMETERS IN THE APPROACH TO THE TREATMENT OF RICKETS (European Journal of Interdisciplinary Research and Development, 2024)
The correct tactics for the treatment of rickets is an indispensable component of the correction of disorders of phosphorus-calcium metabolism in a growing child in modern conditions. 203 children under the age of 1 year were examined. In all children, the level of 25(OH)D in the blood serum, the level of calcium and phosphorus were determined. The proposed scheme of individual prescription of vitamin D preparations for children with rickets in combination with calcium preparations and general strengthening therapy made it possible to significantly increase the effectiveness of treatment. At the same time, there is a decrease in the clinical manifestations of rickets, its residual effects, symptoms of spasmophilia and an increase in the content of 25(OH)D3 in the blood serum.